Variants in the CYP7B1 gene region do not affect natural resistance to HIV-1 infection (2015)
ABSTRACT: Background: The genetic bases of natural resistance to HIV-1 infection remain largely unknown. Recently, two genome-wide association studies suggested a role for variants within or in the vicinity of the CYP7B1 gene in modulating HIV susceptibility. CYP7B1 is an appealing candidate for this due to its contribution to antiviral immune responses. We analyzed the frequency of two previously described CYP7B1 variants (rs6996198 and rs10808739) in three independent cohorts of HIV-1 infected subjects and HIV-1 exposed seronegative individuals (HESN). Findings: rs6996198 and rs10808739 were genotyped in three case/control cohorts of sexually-exposed HESN and HIV-1-infected individuals from Italy, Peru and Colombia. Comparison of the allele and genotype frequencies of the two SNPs under different models showed that the only significant difference was seen for rs6996198 in the Peruvian sample (nominal p = 0.048, dominant model). For this variant, a random-effect meta-analysis yielded non-significant results (dominant model, p = 0.78) and revealed substantial heterogeneity among cohorts. No significant effect of the rs10808739 allelic status on HIV-1 infection susceptibility (additive model, p = 0.30) emerged from the meta-analysis. Conclusions: Although our study had limited power to detect association due to the small sample size, comparisons among the three cohorts revealed very similar allelic and genotypic frequencies in HESN and HIV-1 positive subjects. Overall, these data indicate that the two GWAS-defined variants in the CYP7B1 region do not strongly influence HIV-1 infection susceptibility